Eurocentrism in “The Heart of Darkness” by Joseph Conrad” - Razak, Muhammad Fauzi; Riskiawati, Nur Sapta (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research addresses to analyze Eurocentrism in “Joseph Conrad’s Heart of Darkness. The type of this research is descriptive qualitative. Data were classified into primary and supporting data. The primary data were mainly from the Conrad’s Heart of Darkness. The supporting data were from books, articles, and journals related to colonialism perspective. The design of this research focuses in revealing the colonial life in Conrad’s Heart of Darkness through Eurocentrism perspective. The result of this research is this colonization actually begun not only by economy factor but also it is empowered by creating discourse about such colonized country. Colonial discourse means how the west, colonizer or conquer create opinion to legitimate their conquest. This discourse also explains how the Europe (colonizer) constructs their identity and their colonized. This constructing creates binary-opposition judgment where in this novel through Marlow (as main character) depict that Europe’s colonization is based on their negative stereotyping. It is stated that the native Congo is wilder, cannibal, uncivilized and so on. So, at Marlow’s spirit in early they (colonizer) desire to civilize them (the native).